2016
DOI: 10.1038/srep39108
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of phosphate in water using one-step synthesized zirconium-loaded reduced graphene oxide

Abstract: In this account, a one-step green hydrothermal method for zirconium-loaded reduced graphene oxide (RGO-Zr) adsorbent was developed in pure water. It is based on the formation of initially strong-coupling RGO-Zr nanocomposites followed by in situ reduction of GO to RGO during the hydrothermal treatment. The phosphate adsorption performance of the as-prepared nanocomposites was investigated in aqueous environment under various conditions. The characterization results of RGO-Zr nanocomposites showed that ZrO2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 49 publications
3
35
0
Order By: Relevance
“…Therefore, the adsorption of phosphates by iron oxide loaded chitosan-cellulose acetate particles followed the pseudo second order kinetic model, and it suggests that chemisorption, involving valence shared or electron exchange between adsorbate and adsorbent is what the adsorption is based on [24]. Similar observations have also been report in other studies [15] [25] [26]. In general, the regression for all three models was found to be R 2 > 0.9 and hence the results suggest both physical and chemical adsorption might be involved in the adsorption process.…”
Section: Adsorption Kineticssupporting
confidence: 84%
“…Therefore, the adsorption of phosphates by iron oxide loaded chitosan-cellulose acetate particles followed the pseudo second order kinetic model, and it suggests that chemisorption, involving valence shared or electron exchange between adsorbate and adsorbent is what the adsorption is based on [24]. Similar observations have also been report in other studies [15] [25] [26]. In general, the regression for all three models was found to be R 2 > 0.9 and hence the results suggest both physical and chemical adsorption might be involved in the adsorption process.…”
Section: Adsorption Kineticssupporting
confidence: 84%
“…The adsorption kinetics for all three contaminants were better described by the pseudo-second-order model, i.e., the rate of adsorption was proportional to the square of the number of unoccupied sites on the surface of Al-Mg/GO composites and to the concentration of contaminants in the solution. Similar kinetic results have been reported for adsorbing these contaminants on the surface of different adsorbents [21,30,58]. The pH evolution during the adsorption process exhibited the same trend (approaching the pH pzc ) for all three contaminants (Fig.…”
Section: Adsorption Isotherms and Kineticssupporting
confidence: 84%
“…Therefore, a simple, green, and scalable method is needed to synthesize separation-free GO-based composites for runoff quality control. A recent study reported a one-step synthesis of Zr-loaded rGO for phosphate adsorption, indicating the feasibility of developing multifunctional GO-based adsorptive materials via facile procedures for stormwater management [30].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the component couldpartially be related to water chemisorption and formation of surface hydroxide species Zr(OH) 4 . 62 The analyzed C 1s peak can be curve-fitted with three components at 284.6, 286.5 and 288.6 eV ascribed to adventitious carbon and tartrate species. 61,63 The analysis was summarized in Table 1.…”
Section: Xps Studiesmentioning
confidence: 97%